2021
DOI: 10.1002/ejoc.202100981
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Half‐Salen Complexes: Synthesis, Structural Characterization and Studies as Catalysts for rac‐Lactide Ring‐Opening Polymerization

Abstract: Seven lithium complexes supported by sterically and electronically diverse phenoxyimine ligands were synthesized and characterized by X-ray diffraction, NMR spectroscopy and elemental microanalysis. These complexes show high activity (k obs � 7.43 × 10 À 2 s À 1 ) for rac-lactide ring-opening polymerization (ROP) in the presence of co-initiator benzyl alcohol (BnOH), with the exception of Li4 which features an unusual polymeric ladder structure. Overall, the catalyst activity correlates to the aggregation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 72 publications
(159 reference statements)
4
16
0
Order By: Relevance
“…Sodium (and indeed other alkali metal) complexes typically display very high catalytic activities in rac ‐LA ROP, yet often give poor control over the molecular weight and dispersity [17] . Previous studies have suggested that alkali metal complexes can simultaneously operate through two different LA ROP mechanisms (coordination‐insertion and activated monomer) in the presence of an exogeneous alcohol, a factor which may be partially responsible for the poor polymerisation control [15,16] . Indeed, poor control occurs with [LNa 3 ] ; a bimodal distribution and broad dispersities are observed after 50 s (Table 1, entry 4; Table S5, entries 9–15).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sodium (and indeed other alkali metal) complexes typically display very high catalytic activities in rac ‐LA ROP, yet often give poor control over the molecular weight and dispersity [17] . Previous studies have suggested that alkali metal complexes can simultaneously operate through two different LA ROP mechanisms (coordination‐insertion and activated monomer) in the presence of an exogeneous alcohol, a factor which may be partially responsible for the poor polymerisation control [15,16] . Indeed, poor control occurs with [LNa 3 ] ; a bimodal distribution and broad dispersities are observed after 50 s (Table 1, entry 4; Table S5, entries 9–15).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether initiation with [LNaAlMe] /BnOH occurred via an activated monomer mechanism (where nucleophilic attack of LA occurs from an exogeneous alcohol) or a coordination insertion mechanism (where nucleophilic attack occurs from a metal‐alkoxide unit), [15] the reaction between [LNaAlMe] and BnOH (1 : 1 ratio) was investigated. For consistency with the polymerisation conditions, the stoichiometric reaction was performed in toluene solvent at room temperature and then analysed in CDCl 3 solvent due to the poor solubility of [LNaAlMe] in d 8 ‐toluene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of pyridine within the heteroleptic complexes appeared to increase the rate of polymerization while giving rise to the formation of a broad mixture of polymer structures including low M n of cyclic PLA. At this stage, it is difficult to propose a mechanism because the polymerization of lactide with these systems could be based on a coordinationinsertion or activated monomer process, which could also involve one of the two ligands (e. g. Li, [37] Na [38] or Zn [36] systems). Also, we cannot exclude that the mechanism could occur by zwitterionic ROP (e. g. N-heterocycle carbene, [39] Ce(III)À NHC complexes, [40] ) or a ring-expansion polymerization process (e. g. Ln, [41] Bi, [42] Sn [43] complexes).…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, it is difficult to propose a mechanism because the polymerization of lactide with these systems could be based on a coordination‐insertion or activated monomer process, which could also involve one of the two ligands ( e. g . Li, [37] Na [38] or Zn [36] systems). Also, we cannot exclude that the mechanism could occur by zwitterionic ROP ( e. g .…”
Section: Discussionmentioning
confidence: 99%